2020
DOI: 10.1021/acs.langmuir.0c01803
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide Sensing in Water Using a Copper Metallogel through “Turn-on” Fluorescence

Abstract: The development of fluorescent probes for selective detection of cyanide has gained considerable attention over the past two decades due to benefits like high selectivity as well as sensitivity, fast response, visual output, accurate quantification, and a simplified sample preparation procedure. However, the propensity of supramolecular gels toward fluorescence sensing of cyanide in aqueous medium is not well explored until now. Herein, we report the design and synthesis of a novel copper based metallogel capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…[341][342][343][344] In a recent study, Sebastian and Prasad synthesized a Cu-gel of a terpyridine linked poly(aryl ether) dendrone. 345 The nonemissive spectra of the Cu-gel was selectively turned on in presence of CN À ion. As suggested, scavenging of Cu 2+ from the gel fibres by CN À ions through the formation of [Cu (CN) x ] nÀ complex led to attend the original gelation attributes of the poly(aryl ether) dendrone gelator which resulted in significant enhancement in the emission of the gel.…”
Section: (Vii) Post Assembly Fabrication Of Gels By Chemical Analytesmentioning
confidence: 99%
“…[341][342][343][344] In a recent study, Sebastian and Prasad synthesized a Cu-gel of a terpyridine linked poly(aryl ether) dendrone. 345 The nonemissive spectra of the Cu-gel was selectively turned on in presence of CN À ion. As suggested, scavenging of Cu 2+ from the gel fibres by CN À ions through the formation of [Cu (CN) x ] nÀ complex led to attend the original gelation attributes of the poly(aryl ether) dendrone gelator which resulted in significant enhancement in the emission of the gel.…”
Section: (Vii) Post Assembly Fabrication Of Gels By Chemical Analytesmentioning
confidence: 99%
“…Recently, many studies have shown the use of Cu 2+ complexes as a probe for the optical detection of anions such as cyanide (CN À ) and biological phosphates such as PPi and ATP in semiaqueous and aqueous solutions. 19,20,[24][25][26][27][28][29][30][31][32][33][34][35]36 Most of the small organic molecule-based cyanide probes have the disadvantage of water solubility; therefore, the use of organic solvent as a cosolvent is unavoidable. [37][38][39] The probe Lipo-1 works in a pure aqueous solution to detect copper with a good change in the emission signal.…”
Section: Binding Studies Of Lipo-1cu With Anionsmentioning
confidence: 99%
“…Among the pioneering examples of microfluidic integration is the supramolecular optical chemosensor by Nocera and co-workers, which uses cyclodextrin modified with a Tb 3+ macrocycle to detect polyaromatic hydrocarbons in aqueous solutions at sub-micromolar concentrations even without signal amplification ( Rudzinski et al, 2002 ). Recently, gel-based supramolecular sensors have been emerging as a platform that provides a unique kinetics and dynamics for the sensing process ( Cao et al, 2019 ; Ma et al, 2019 ; Sebastian and Prasad, 2020 ). For example, supramolecular copper metallogel has been used for sensing toxic cyanide ions ( Sebastian and Prasad, 2020 ).…”
Section: Emerging Trends and Current Challengesmentioning
confidence: 99%
“…Recently, gel-based supramolecular sensors have been emerging as a platform that provides a unique kinetics and dynamics for the sensing process ( Cao et al, 2019 ; Ma et al, 2019 ; Sebastian and Prasad, 2020 ). For example, supramolecular copper metallogel has been used for sensing toxic cyanide ions ( Sebastian and Prasad, 2020 ). This work presented cyanide sensing based on deprotonation in aqueous medium caused by very high solvation energy of cyanide ion in water.…”
Section: Emerging Trends and Current Challengesmentioning
confidence: 99%